An Enigmatic Stramenopile Sheds Light on Early Evolution in Ochrophyta Plastid Organellogenesis. (28th March 2022) - Azuma, Tomonori; Pánek, Tomáš; Tice, Alexander K.; Kayama, Motoki; Kobayashi, Mayumi; Miyashita, Hideaki; Suzaki, Toshinobu; Yabuki, Akinori; Brown, Matthew W.; Kamikawa, Ryoma
Abstract: Ochrophyta is an algal group belonging to the Stramenopiles and comprises diverse lineages of algae which contribute significantly to the oceanic ecosystems as primary producers. However, early evolution of the plastid organelle in Ochrophyta is not fully understood. In this study, we provide a well-supported tree of the Stramenopiles inferred by the large-scale phylogenomic analysis that unveils the eukaryvorous (nonphotosynthetic) protist Actinophrys sol (Actinophryidae) is closely related to Ochrophyta. We used genomic and transcriptomic data generated from A. sol to detect molecular traits of its plastid and we found no evidence of plastid genome and plastid-mediated biosynthesis, consistent with previous ultrastructural studies that did not identify any plastids in Actinophryidae. Moreover, our phylogenetic analyses of particular biosynthetic pathways provide no evidence of a current and past plastid in A. sol . However, we found more than a dozen organellar aminoacyl-tRNA synthases (aaRSs) that are of algal origin. Close relationships between aaRS from A . sol and their ochrophyte homologs document gene transfer of algal genes that happened before the divergence of Actinophryidae and Ochrophyta lineages. We further showed experimentally that organellar aaRSs of A. sol are targeted exclusively to mitochondria, although organellar aaRSs in Ochrophyta are dually targeted to mitochondria and plastids. Together, our findings suggested that the last common ancestor of Actinophryidae and Ochrophyta had not yet completed the establishment of host–plastid partnership as seen in the current Ochrophyta species, but acquired at least certain nuclear-encoded genes for the plastid functions.